New records of Euglenophyceae from Sylhet division, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2021)
A total of 8 species of Euglenophyceae where 5 species of Euglena namely, Euglena lucens Günther, E. paludosa Mainx., E. gaumei Allorge & Lefèvre , E. heimii Lef., E. mangini Lefévre, and 3 species of Lepocinclis namely, Lepocinclis ovum var. deflandriana (Ehrenberg) Lemmermann, L. ovum var. globulus ( Perty) Lemmermann and L. steinii Lemmermann from Sylhet Division which are all new records for Bangladesh.Bangladesh J. Plant Taxon. 28(1): 11-15, 2021 (June)